High-radiation-resistance aluminum alloy material and preparation method thereof

The high radiation-resistant aluminum alloy material prepared by arc melting contains a specific molar ratio of aluminum, nickel, cobalt, iron and chromium elements to form matrix and fiber phases, solving the problems of poor radiation resistance and high density of traditional aluminum alloys, and achieving efficient radiation resistance and low-cost applications.

CN119800162APending Publication Date: 2025-04-11PEKING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411771956.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Traditional aluminum alloys have low radiation resistance and high density in high radiation environments, which increases transportation and installation costs.

Method used

Arc smelting method is used to prepare a high-irradiation-resistant aluminum alloy material, containing aluminum, nickel, cobalt, iron and chromium elements, with a molar ratio of (90-96): (1-2.5): (1-2.5): (1-2.5): (1-2.5): (1-2.5): (1-2.5). The matrix and fiber phase are formed, and nickel, cobalt, iron and chromium elements are enriched in the fiber phase.

Benefits of technology

High radiation resistance and low density are achieved, reducing transportation and installation costs while maintaining good mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800162A_ABST
    Figure CN119800162A_ABST
Patent Text Reader

Abstract

The invention discloses a high-radiation-resistance aluminum alloy material and a preparation method thereof. The high-radiation-resistance aluminum alloy material contains an aluminum element, a nickel element, a cobalt element, an iron element and a chromium element, the molar ratio of the aluminum element to the nickel element to the cobalt element to the iron element to the chromium element is (90-96): (1-2.5): (1-2.5): (1-2.5): (1-2.5), the high-radiation-resistance aluminum alloy material comprises a base body and a fiber phase, the fiber phase is distributed in the base body, and the fiber phase is a fiber phase. The nickel element, the cobalt element, the iron element and the chromium element are enriched in the fiber phase. Therefore, the high-radiation-resistance aluminum alloy material has the advantages of a multi-component alloy and an aluminum alloy, is low in density and has relatively high radiation resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of materials, and in particular to a high-radiation-resistant aluminum alloy material and a preparation method thereof. Background Art

[0002] Nuclear energy has become the world's third largest source of electricity after thermal power and hydropower due to its cleanliness, economy and reliability. Structural materials used in nuclear power plants are usually required to have a variety of properties, among which the radiation resistance of nuclear fuel cladding materials is particularly important, because high-dose irradiation can lead to irradiation-induced defects such as vacancies and interstitial atoms, which may further evolve into microstructural defects such as voids and dislocation loops, leading to the degradation of the macroscopic properties of the material.

[0003] In recent years, multi-component alloys, as a new type of alloy based on the equiatomic ratio of several main elements, have been widely studied and applied. Compared with traditional alloys based on one or two main elements, multi-component alloys usually contain five or more main elements. Due to their complexity of composition and lattice distortion effect, multi-component alloys can change the formation energy, migration barrier and diffusion path of irradiation-induced defects, thereby inhibiting the accumulation of defects, making them have good prospects in the application of radiation-resistant structural materials. However, the composition of traditional Cantor multi-component alloys usually includes high-density iron, cobalt, nickel, chromium, manganese and other elements, which are heavy, which not only increases the cost of transportation and installation, but also increases the complexity of the supporting structure. Aluminum alloys, especially high-strength aluminum alloys, have wide application potential due to their low density, high strength and hardness. However, the radiation resistance of traditional aluminum alloys in high-irradiation environments is relatively low. The atomic number of aluminum is low, which leads to its relatively simple crystal structure, making the aluminum alloy more susceptible to radiation damage. In addition, the low vacancy formation energy of aluminum also leads to its poor radiation resistance, because the low vacancy formation energy is easy to produce defects such as vacancies and dislocations, thereby leading to the degradation of mechanical properties.

[0004] Therefore, if the unique properties of multi-component alloys can be incorporated into traditional aluminum alloys, it can open up new possibilities for structural materials in the development of nuclear reactor technology. Summary of the invention

[0005] The present invention aims to alleviate or solve at least one of the above-mentioned problems to at least some extent.

[0006] In one aspect of the present invention, the present invention proposes a highly radiation-resistant aluminum alloy material. In some embodiments of the present invention, the highly radiation-resistant aluminum alloy material contains aluminum, nickel, cobalt, iron and chromium, and the molar ratio of aluminum, nickel, cobalt, iron and chromium is (90-96):(1-2.5):(1-2.5):(1-2.5):(1-2.5), and the highly radiation-resistant aluminum alloy material includes a matrix and a fiber phase, the fiber phase is distributed in the matrix, and nickel, cobalt, iron and chromium are enriched in the fiber phase. As a result, the highly radiation-resistant aluminum alloy material has the advantages of both multi-component alloys and aluminum alloys, has low density, and has high radiation resistance.

[0007] In some embodiments of the present invention, the diameter of the fiber phase is 60 nm to 210 nm.

[0008] In some embodiments of the present invention, the length of the fiber phase is 158 nm to 3.5 μm.

[0009] In some embodiments of the present invention, in the high radiation-resistant aluminum alloy material, the molar ratio of aluminum element, nickel element, cobalt element, iron element and chromium element is 96:1:1:1:1.

[0010] In another aspect of the present invention, the present invention proposes a method for preparing a highly radiation-resistant aluminum alloy material. In some embodiments of the present invention, the raw materials aluminum, nickel, cobalt, iron, and chromium are smelted into a highly radiation-resistant aluminum alloy material by an arc melting method, and the molar ratio of aluminum, nickel, cobalt, iron, and chromium in the raw materials is (90-96): (1-2.5): (1-2.5): (1-2.5): (1-2.5), and the current used for arc melting is 350A-450A, each melting is 30s-40s, and the melting is repeated 10-30 times, and the surface is turned over after each melting. Thus, the highly radiation-resistant aluminum alloy material prepared by the method has a matrix and a fiber phase, and nickel, cobalt, iron, and chromium are enriched in the fiber phase. The fiber phase is a multi-component alloy and has high radiation resistance. The highly radiation-resistant aluminum alloy material has a low density and is used as a radiation-resistant material, which is conducive to reducing transportation and installation costs.

[0011] In some embodiments of the present invention, the molar ratio of aluminum, nickel, cobalt, iron and chromium in the raw material is 96:1:1:1:1.

[0012] In some embodiments of the present invention, the current used for arc melting is 400A, each melting lasts 35s, and the melting is repeated 20 times.

[0013] In some embodiments of the present invention, the purity of aluminum, nickel, cobalt, iron and chromium in the raw materials is ≥99.99%.

[0014] In some embodiments of the present invention, the reaction chamber is evacuated to 3×10 -3 Below Pa, fill with protective gas.

[0015] In some embodiments of the present invention, the titanium ingot is first smelted before smelting to remove impurities in the reaction chamber. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0017] Figure 1 Figures (a), (b), and (c) respectively show the SEM image, STEM-BF image, and STEM-HAADF image of the unirradiated original aluminum alloy material in Example 1;

[0018] Figure 2 Figures (d), (e), and (f) respectively show the STEM-BF images of the aluminum alloy material in Example 1 at different magnifications after 50 dpa aluminum ion irradiation; Figure 2 Figures (g), (h), and (i) in the figure respectively show the STEM-HAADF images of the aluminum alloy material in Example 1 at different magnifications after 50 dpa aluminum ion irradiation;

[0019] Figure 3 Figure (a1) shows the STEM-HAADF image of the unirradiated original aluminum alloy material in Example 1; Figure 3 Figures (a2), (a3), (a4), (a5), and (a6) respectively show the EDS element distribution images of aluminum, chromium, iron, cobalt, and nickel elements of the unirradiated original aluminum alloy material in Example 1;

[0020] Figure 4 Figure (b1) shows the STEM-HAADF image of the aluminum alloy material in Example 1 after 50 dpa aluminum ion irradiation; Figure 4 Figures (b2), (b3), (b4), (b5), and (b6) respectively show the EDS element distribution images of aluminum, chromium, iron, cobalt, and nickel in the aluminum alloy material in Example 1 after 50 dpa aluminum ion irradiation;

[0021] Figure 5 Figure (c1) shows the Ni, Co, Fe and Cr elements in the unirradiated original aluminum alloy material in Example 1. Figure 3 The line scan atomic ratio corresponding to the dashed arrow in Figure (a1) is Figure 5Figure (c2) shows the Ni, Co, Fe and Cr elements of the aluminum alloy material in Example 1 before and after 50dpa aluminum ion irradiation. Figure 4 The line scan atomic ratio corresponding to the dotted arrow in Figure (b1);

[0022] Figure 6 Figures (a) and (b) show the TEM images of pure aluminum and the aluminum alloy material in Example 1 after irradiation with 50 dpa aluminum ions, respectively. DETAILED DESCRIPTION

[0023] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.

[0024] In one aspect of the present invention, the present invention provides a highly radiation-resistant aluminum alloy material. In some embodiments of the present invention, the highly radiation-resistant aluminum alloy material contains aluminum, nickel, cobalt, iron and chromium, and the molar ratio of aluminum, nickel, cobalt, iron and chromium is (90-96):(1-2.5):(1-2.5):(1-2.5):(1-2.5), with reference to Figure 1 and Figure 3 The highly radiation-resistant aluminum alloy material includes a matrix and a fiber phase (multi-component fiber). The fiber phase (multi-component fiber) is distributed in the matrix, and nickel, cobalt, iron, and chromium are enriched in the fiber phase. Each element in the highly radiation-resistant aluminum alloy material is distributed in the matrix and the fiber phase. Nickel, cobalt, iron, and chromium are enriched in the fiber phase. When irradiated, the fiber phase can resist irradiation due to its own structural characteristics and atomic exchange mechanism, making it difficult for the aluminum alloy material to produce defects such as vacancies and can maintain good mechanical properties; the material has a low density, is easy to transport and install, and is conducive to saving transportation and installation costs.

[0025] In some embodiments of the present invention, the fiber phase may be a multi-component high entropy fiber.

[0026] In some embodiments of the present invention, in the high radiation-resistant aluminum alloy material, the molar ratio of aluminum element, nickel element, cobalt element, iron element and chromium element may be 96:1:1:1:1.

[0027] In some other embodiments of the present invention, in the high radiation-resistant aluminum alloy material, the molar ratio of aluminum element, nickel element, cobalt element, iron element and chromium element can be 90:2.5:2.5:2.5:2.5.

[0028] In some other embodiments of the present invention, in the high radiation-resistant aluminum alloy material, the molar ratio of aluminum element, nickel element, cobalt element, iron element and chromium element can be 94:1.5:1.5:1.5:1.5.

[0029] In some embodiments of the present invention, the diameter of the fiber phase may be 60 nm to 210 nm. For example, the diameter of the fiber phase may be 60 nm, 80 nm, 100 nm, 150 nm, 180 nm, 210 nm, etc.

[0030] In some embodiments of the present invention, the length of the fiber phase may be 158 nm to 3.5 μm. For example, the length of the fiber phase may be 158 nm, 200 nm, 500 nm, 800 nm, 1 μm, 2 μm, 3.5 μm, etc.

[0031] In another aspect of the present invention, the present invention proposes a method for preparing a highly radiation-resistant aluminum alloy material. In some embodiments of the present invention, the raw materials aluminum, nickel, cobalt, iron, and chromium can be smelted into a highly radiation-resistant aluminum alloy material by an arc melting method, and the molar ratio of aluminum, nickel, cobalt, iron, and chromium in the raw materials can be (90-96): (1-2.5): (1-2.5): (1-2.5): (1-2.5). Adding the raw materials according to the above ratio and smelting by an arc melting method is conducive to forming a highly radiation-resistant aluminum alloy material containing a fiber phase, and the fiber phase is evenly distributed in the matrix.

[0032] In some embodiments of the present invention, the molar ratio of aluminum, nickel, cobalt, iron and chromium in the raw material can be 96:1:1:1:1.

[0033] In other embodiments of the present invention, the molar ratio of aluminum, nickel, cobalt, iron and chromium in the raw materials can be 90:2.5:2.5:2.5:2.5.

[0034] In other embodiments of the present invention, the molar ratio of aluminum, nickel, cobalt, iron and chromium in the raw materials can be 94:1.5:1.5:1.5:1.5.

[0035] In some embodiments of the present invention, when arc melting is used to prepare a high radiation resistant aluminum alloy material, the current used for arc melting can be 350A to 450A, each melting is 30s to 40s, and the melting is repeated 10 to 30 times, and the material is turned over after each melting. In some embodiments, the current used for arc melting can be 350A, 370A, 390A, 400A, 420A, 430A, 450A, etc., the time for each melting can be 30s, 32s, 35s, 37s, 40s, etc., and the number of repeated meltings can be 10 times, 15 times, 20 times, 25 times, 30 times, etc. Therefore, the current within the above range is conducive to the melting of the raw materials. After multiple meltings and repeated turnings, the elements can be mixed evenly, which is conducive to improving the uniformity of the high radiation resistant aluminum alloy material, and precipitating the fiber phase, thereby obtaining a multi-component fiber-reinforced aluminum alloy material.

[0036] In some embodiments of the present invention, aluminum, nickel, cobalt, iron, and chromium can all be cylindrical metal particles in the raw materials. The raw materials in the above shapes can be mixed evenly during repeated smelting and produce a fiber phase; the cylindrical metal particles can be melted evenly during the smelting process, which helps to achieve uniform distribution of each component and also helps to reduce the generation of impurities.

[0037] In some specific embodiments of the present invention, the current used for arc melting can be 400A, each melting is 35s, and the melting is repeated 20 times, and the surface is turned over after each melting. Arc melting of the raw materials using the above parameters can make the raw materials fully mixed and uniform, and generate a multi-component fiber phase during the melting process, so that the prepared aluminum alloy material has both light weight and radiation resistance.

[0038] In some embodiments of the present invention, the purity of aluminum, nickel, cobalt, iron and chromium in the raw materials is ≥99.99%, and the purity of each element particle in the raw materials is higher than 99.99%, which is beneficial to improve the purity of the product and reduce the content of impurity elements in the product.

[0039] In some embodiments of the present invention, before melting the raw materials, the reaction chamber may be evacuated to a vacuum of 3×10 -3 Pa, a protective gas (such as argon, etc.) is filled in to avoid the introduction of impurity elements in the air during the reaction.

[0040] In some embodiments of the present invention, before melting the raw materials, the titanium ingot may be firstly melted to remove impurities (such as impurity elements such as C, N, and O) in the reaction chamber.

[0041] In some embodiments of the present invention, before melting the raw materials, the reaction chamber can be evacuated to 3×10 -3Pa, fill in protective gas argon to close to normal pressure, and then melt the titanium ingot once more to remove impurity elements such as C, N, and O in the reaction chamber.

[0042] It should be noted that the aluminum alloy ingot prepared by the vacuum arc melting method in the present invention can be in the shape of a round cake or a cylinder, and can be subsequently processed into a desired shape and size according to the needs of actual application.

[0043] The highly radiation-resistant aluminum alloy material proposed in the present invention can be applied to structures requiring radiation-resistant performance, for example, can be used as a material for nuclear fuel cladding.

[0044] The present invention will be described below by specific examples, and it will be appreciated by those skilled in the art that the following specific examples are only for illustrative purposes, and do not limit the scope of the present invention in any way. In addition, in the following examples, unless otherwise specified, the materials and equipment used are all commercially available. If in the following examples, specific processing conditions and processing methods are not clearly described, then conditions and methods known in the art can be used to process.

[0045] Example 1

[0046] Aluminum alloy materials are prepared by vacuum arc melting, wherein the purity of the five raw materials aluminum, iron, cobalt, nickel, and chromium used in melting is higher than 99.99%, and the weight of each element raw material is weighed by a high-precision electronic balance, and the error is within ±0.005g. Among the raw materials, the diameter of the cylindrical aluminum metal particles is 4mm and the length is 10mm, the diameter of the iron, cobalt, nickel, and chromium metal particles is 3mm and the length is 3mm, and the molar ratio of aluminum, nickel, cobalt, iron, and chromium is 96:1:1:1:1.

[0047] First, evacuate the furnace chamber to 3×10 -3 Pa, argon is filled as a protective gas, and Ti ingots are melted before smelting to remove impurity elements such as C, N, and O in the furnace chamber. After that, arc melting of aluminum, nickel, cobalt, iron, and chromium raw materials is started. During each arc melting, the current machine provides current of 50A, and each melting time is 35s. The ingot is turned over and smelted repeatedly for 20 times to make the elements evenly mixed to obtain a round cake-shaped ingot.

[0048] In order to facilitate the subsequent observation of the microstructure of the product, after obtaining the round cake-shaped ingot, the round cake-shaped ingot was sucked into a cylindrical metal ingot through a copper suction casting mold. The diameter of the cylindrical metal ingot is 6 mm and the length is 30 mm. The cylindrical metal ingot is cut into thin slices with a thickness of 1 mm, polished with SiC sandpaper, and mechanically polished to obtain a mirror effect. Next, electrochemical polishing is performed using a mixed solution of 70% methanol, 20% perchloric acid, and 10% ethanol (volume ratio) to eliminate tiny scratches and surface stress layers on the sample surface.

[0049] Pure aluminum was used as a control sample. Irradiation experiments were carried out on pure aluminum and the aluminum alloy material prepared in Example 1. 3MeV aluminum ion irradiation was carried out on a 2×1.7MV tandem accelerator. The irradiation damage reached 50dpa. The irradiation temperature was 150°C. During the irradiation process, the vacuum degree of the sample chamber was less than 1×10 -4 Pa.

[0050] The cross-sectional microstructure of the sample of Example 1 before irradiation was characterized using a field emission environmental scanning electron microscope (SEM, ThermoFisher Quattro ESEM, ThermoFisher, USA). The cross-sectional microstructure of the sample of Example 1 before and after irradiation was characterized using a transmission electron microscope (TEM, spherical aberration corrected electron microscope Titan Cubed Themis G2, FEI, USA, accelerating voltage 300 kV, convergence half angle 23.5 mrad) (bright field (STEM-BF) and high angle annular dark field (STEM-HAADF) imaging modes were used, respectively).

[0051] The cross-sectional microstructure of the irradiated samples was characterized using a field emission environmental scanning electron microscope (SEM, ThermoFisher Quattro ESEM, ThermoFisher, USA) and a transmission electron microscope (TEM, FEI, USA, spherical aberration-corrected electron microscope Titan Cubed Themis G2, accelerating voltage 300 kV, convergence half angle 23.5 mrad) (bright field (STEM-BF) and high angle annular dark field (STEM-HAADF) imaging modes were used, respectively). The dislocation rings caused by irradiation were observed by STEM-BF characterization, which can effectively eliminate most of the diffraction contrast caused by equal thickness fringes and improve the image quality of irradiation defects. At the same time, low beam current X-ray energy dispersive spectroscopy (EDS) was used to analyze the chemical composition of the samples to obtain element distribution images of each element before and after irradiation.

[0052] Among them, the TEM cross-section samples were prepared by focused ion beam (FIB) extraction technology. During the FIB process, the slices were thinned using 30kV Ga ions (current range 0.77 to 9.1nA), and finally cleaned with 2kV Ga ions (current 44pA) to remove the amorphous layer and accidental damage introduced by the thinning process. It should be noted that when conducting a comparative analysis of irradiated samples and non-irradiated samples, the irradiation target chamber was evacuated and heated to 150°C for 11 hours during the aluminum ion irradiation process. In order to create the same environment as the irradiation target chamber, the unirradiated samples of Example 1 were vacuum annealed at the same temperature and time before microstructural characterization.

[0053] Figure 1 Figures (a), (b) and (c) in the figure respectively show the SEM image (scanning electron microscope image), STEM-BF image (bright field image) and STEM-HAADF image (high angle annular dark field image) of the unirradiated original aluminum alloy sample in Example 1. Figure 1 It can be clearly observed from Figures (a), (b) and (c) in that the aluminum alloy sample of Example 1 includes a matrix and a strip-shaped precipitation phase distributed in the matrix, that is, a fiber phase (multi-component high entropy fiber); Figure 1 As can be seen in Figure (b), near the precipitated phase indicated by the green arrow, there is a sparse distribution of dislocation lines due to the internal stress generated by the multi-component high entropy fibers in the matrix.

[0054] Figure 2 Figures (d), (e), and (f) are STEM-BF images of the sample cross section of the aluminum alloy material in Example 1 at different magnifications after being irradiated with aluminum ions at 50 dpa, respectively. Figure 2 Figures (g), (h), and (i) are STEM-HAADF images of the sample cross section of the aluminum alloy material in Example 1 at different magnifications after 50 dpa aluminum ion irradiation. Figure 2 In both (d) and (g), the boundary between the damaged area and the non-irradiated area can be seen (red dashed line). Figure 2 Figures (e) and (h) show more detailed observations of the irradiated damaged region by STEM-BF and STEM-HAADF, where high-density dislocation loops are uniformly distributed throughout the region, while in the non-irradiated region (e.g. Figure 2No dislocation loops were observed in (f) and (i) of the figure. In the damaged area and the unirradiated area, fibrous particles are distributed in the matrix. By comparing the multicomponent high entropy fibers in the damaged area and the unirradiated area, it can be clearly found that after aluminum ion irradiation, the diameter size of the multicomponent high entropy fibers is enlarged and the number density of the multicomponent high entropy fibers is reduced. The shape of the multicomponent high entropy fibers is also different before and after irradiation: before irradiation, the multicomponent high entropy fibers have a tubular cylindrical structure, while after irradiation, the multicomponent high entropy fibers are "filled" and expanded, becoming an elliptical structure.

[0055] The change of elements in the fiber phase can also be achieved by Figure 2 The contrast change of the fiber phase in Figure (g) is verified. Since STEM-HAADF collects incoherent scattered electrons and has a strong atomic number contrast (i.e., Z contrast), the multicomponent high entropy fibers in the unirradiated area are obviously brighter and have a stronger contrast than the multicomponent high entropy fibers in the irradiated damaged area. Therefore, the Cr-rich unirradiated multicomponent high entropy fibers (Cr has a larger atomic number) show a stronger contrast than the irradiated multicomponent high entropy fibers because the Cr in the latter has been replaced by lighter Al. It should be noted that the elements in each multicomponent high entropy fiber are slightly different, and the quantitative content is not fixed, but is within a reasonable fluctuation range.

[0056] Figure 3 Figure (a1) shows the STEM-HAADF image of the original aluminum alloy material without irradiation. Figure 3 Figures (a2) to (a6) show the distribution images of Al, Cr, Fe, Co, and Ni elements in the unirradiated original aluminum alloy material. It can be seen that Fe, Co, Ni, and Cr tend to be enriched in the fiber phase, while Al is evenly distributed in the matrix.

[0057] Figure 4 Figure (b1) shows the STEM-HAADF image of the aluminum alloy material after 50dpa aluminum ion irradiation. Figure 4 Figures (b2) to (b6) in the figure show the distribution images of Al, Cr, Fe, Co, and Ni elements in the aluminum alloy material after 50dpa aluminum ion irradiation. It can be seen that after irradiation, Fe, Co, and Ni are still enriched in the fiber phase, but Cr is evenly dispersed in the matrix. Therefore, the content of Cr in the fiber phase decreases, and the content of Cr in the matrix increases, but the content of Al in the matrix is ​​much higher than Cr.

[0058] Figure 5Figures (c1) and (c2) in Figure (3) and (4) respectively show the line scan atomic ratios (atomic fractions of Ni, Co, Fe and Cr elements) corresponding to the white dashed arrows in Figure (a1) and Figure (4) to fully demonstrate the composition of the precipitated fiber phase. Figure 5 It can be seen from Figures (c1) and (c2) that after ion irradiation, the content of Cr in the fiber phase is significantly reduced.

[0059] Figure 6 Figures (a) and (b) in the figure show the BF-TEM images (bright field images) of pure aluminum and the aluminum alloy material of Example 1 after aluminum ion irradiation, respectively, taken under the condition of 0.5 μm underfocus. By comparing the two microstructures, it can be clearly seen that a large number of voids can be observed in pure aluminum after ion irradiation, such as Figure 6 As shown in Figure (a), this is the result of the movement, evolution and vacancy aggregation of aluminum interstitial atoms generated by aluminum ion irradiation. However, in the aluminum alloy material of Example 1, no irradiation-induced voids were found. Figure 6 As shown in Figure (b), this indicates that the aluminum alloy material of Example 1 (multi-component high entropy fiber reinforced aluminum alloy) exhibits better radiation resistance than pure aluminum after aluminum ion irradiation. Figure 6 The small figure in the upper right corner of Figure (b) shows the electron diffraction patterns of the matrix and fiber phases under the

[011] crystal zone axis, indicating that a stable disordered solid solution structure has been formed without a superlattice structure.

[0060] In general, a series of experimental studies were conducted on the aluminum alloy containing multi-component high entropy fiber phase with low density and low cost prepared by the present invention, and the following conclusions were drawn: the prepared aluminum alloy material shows a unique microstructure, in which Ni, Co, Fe, and Cr are enriched in fibrous precipitates (fibrous phase), and the fibrous phase is uniformly distributed in the matrix. At 150°C, after 50dpa of aluminum ion irradiation, Fe, Co, and Ni atoms are still enriched in the fiber phase, while the content of Cr atoms in the fiber phase decreases and the content of Cr atoms in the matrix increases. This change in element content is achieved by the process of dynamic exchange of Cr-Al atoms. Since no irradiation-induced voids or swelling phenomena are detected in the aluminum alloy irradiated with aluminum ions, and in pure aluminum, a large number of voids have been observed after ion irradiation, indicating that the aluminum alloy reinforced with multi-component high entropy fibers exhibits higher radiation resistance than pure aluminum.

[0061] In the description of the present invention, the directions or positional relationships indicated by the terms "up", "down", "left", "right", etc. are based on the directions or positional relationships shown in the accompanying drawings and are only for the convenience of describing the present invention rather than requiring that the present invention must be constructed and operated in a specific direction. Therefore, they should not be understood as limitations on the present invention.

[0062] In the description of this specification, the description with reference to the terms "some embodiments", "other embodiments", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment are included in at least one embodiment of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art can combine and combine different embodiments or examples described in this specification and the features of different embodiments or examples without contradiction.

[0063] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A highly radiation-resistant aluminum alloy material, characterized in that: The high radiation resistant aluminum alloy material contains aluminum, nickel, cobalt, iron and chromium, and the molar ratio of aluminum, nickel, cobalt, iron and chromium is (90-96):(1-2.5):(1-2.5):(1-2.5):(1-2.5). The high radiation resistant aluminum alloy material includes a matrix and a fiber phase, the fiber phase is distributed in the matrix, and the nickel, cobalt, iron and chromium are enriched in the fiber phase.

2. The high radiation-resistant aluminum alloy material according to claim 1, characterized in that: The diameter of the fiber phase is 60nm to 210nm.

3. The high radiation-resistant aluminum alloy material according to claim 1, characterized in that: The length of the fiber phase is 158 nm to 3.5 μm.

4. The high radiation-resistant aluminum alloy material according to any one of claims 1 to 3, characterized in that: In the highly radiation-resistant aluminum alloy material, the molar ratio of aluminum element, nickel element, cobalt element, iron element and chromium element is 96:1:1:1:

1.

5. A method for preparing a highly radiation-resistant aluminum alloy material, characterized in that: The raw materials of aluminum, nickel, cobalt, iron and chromium are smelted into high radiation-resistant aluminum alloy material by arc melting method. The molar ratio of aluminum, nickel, cobalt, iron and chromium in the raw materials is (90-96):(1-2.5):(1-2.5):(1-2.5):(1-2.5). The current used for arc melting is 350A-450A. Each melting is 30s-40s. The melting is repeated 10-30 times and the alloy is turned over after each melting.

6. The method according to claim 5, characterized in that The molar ratio of aluminum, nickel, cobalt, iron and chromium in the raw materials is 96:1:1:1:

1.

7. The method according to claim 5, characterized in that The current used for arc melting is 400A, each melting time is 35s, and the melting is repeated 20 times.

8. The method according to any one of claims 5 to 7, characterized in that: Among the raw materials, the purity of aluminum, nickel, cobalt, iron and chromium is ≥99.99%.

9. The method according to any one of claims 5 to 7, characterized in that: Before smelting, the reaction chamber was evacuated to 3×10 -3 Below Pa, fill with protective gas.

10. The method according to any one of claims 5 to 7, characterized in that: Before smelting, the titanium ingot is smelted to remove impurities in the reaction chamber.